2021
DOI: 10.21873/invivo.12498
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders Before and During the COVID-19 Pandemic in Patients Assigned to Adjuvant Radiotherapy for Breast Cancer

Abstract: Background/Aim: The anticipation of radiotherapy can cause distress and sleep disorders, which may be aggravated by the COVID-19 pandemic. This study investigated sleep disorders in a large cohort of patients with breast cancer before and during the pandemic. Patients and Methods: Twenty-three characteristics were retrospectively analyzed for associations with pre-radiotherapy sleep disorders in 338 patients. Moreover, 163 patients presenting before and 175 patients presenting during the COVID-19 pandemic were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
(37 reference statements)
4
13
0
Order By: Relevance
“…Similar to our study, no significant associations were found between sleep disorders and age or previous chemotherapy. Associations between sleep disorders and physical and emotional problems were also found in two previous studies investigating pre-radiotherapy sleep disorders in breast cancer patients (17,18). Moreover, in one of these studies, a trend was observed for an association between sleep disorders and a higher Charlson comorbidity index (17).…”
Section: Discussionsupporting
confidence: 70%
“…Similar to our study, no significant associations were found between sleep disorders and age or previous chemotherapy. Associations between sleep disorders and physical and emotional problems were also found in two previous studies investigating pre-radiotherapy sleep disorders in breast cancer patients (17,18). Moreover, in one of these studies, a trend was observed for an association between sleep disorders and a higher Charlson comorbidity index (17).…”
Section: Discussionsupporting
confidence: 70%
“…In a study of 48 patients scheduled for radiotherapy of prostate cancer, higher distress scores and greater numbers of physical problems were significantly associated with pre-radiotherapy sleep disturbances (21). Moreover, higher distress scores and greater numbers of emotional or physical problems were previously shown in patients irradiated for lung cancer and breast cancer (23,24). Younger age did not prove to be a significant risk factor for pre-treatment sleep disturbances in patients with pelvic malignancies (19)(20)(21) but was significantly associated with the occurrence of preradiotherapy sleep disturbances in previous studies investigating patients irradiated for breast cancer (24) or head-and-neck cancers (25).…”
Section: Discussionmentioning
confidence: 87%
“…Patients included in this study had completed a questionnaire regarding distress (National Comprehensive Cancer Network Distress Thermometer) at the time of the pre-radiotherapy consent discussion with the patients (11). Of these patients who were previously evaluated for sleep disorders (12), 163 presented before and 175 patients during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%